PENGEMBANGAN MEDIA INSEKTARIUM SEBAGAI MEDIA PEMBELAJARAN SMA - Edo Dannyta Sampe Toding; Zulfadli Zulfadli; Listiani Listiani (Biopedagogia, 2021)
This study aims to develop and determine insectarium media's appropriateness as learning media for Class X Senior High School. This study is development research using the ADDIE development model. ADDIE stands for (Analysis-Design-Implement-valuate). The instruments used in this study were the validation sheet and the student response questionnaire sheet. Previously, the product has been validated by material experts, media experts, and biology teachers. Based on the assessment of material experts, media experts, and biology teachers, the product quality is declared excellent and suitable for use as a learning medium. Material experts rated products with a percentage of 80% (feasible category), media experts rated products with a percentage of 80% (feasible category), biology teachers rated products with a very feasible category (94.5%). Meanwhile, the student response obtained an assessment with 82.87% and was categorized as feasible. Therefore, it can be concluded that the insectarium media is suitable for use as a learning medium for class X students.Keywords: Insectarium, Learning Media, Class X Senior High School